The circadian gene, Per2, influences methamphetamine sensitization and reward through the dopaminergic system in the striatum of mice. (9th August 2018) - Kim, Mikyung; Custodio, Raly James; Botanas, Chrislean Jun; de la Peña, June Bryan; Sayson, Leandro Val; Abiero, Arvie; Ryoo, Zae Young; Cheong, Jae Hoon; Kim, Hee Jin
Abstract: Drug addiction is a chronic and relapsing brain disorder, influenced by complex interactions between endogenous and exogenous factors. Per2, a circadian gene, plays a role in drug addiction. Previous studies using Per2 ‐knockout mice have shown a role for Per2 in cocaine, morphine and alcohol addiction. In the present study, we investigated the role of Per2 in methamphetamine (METH) addiction using Per2‐ overexpression and knockout mice. We observed locomotor sensitization responses to METH administration, and rewarding effects using a conditioned place preference test. In addition, we measured expression levels of dopamine and dopamine‐related genes (monoamine oxidase A, DA receptor 1, DA receptor 2, DA active transporter, tyrosine hydroxylase and cAMP response element‐binding protein 1) in the striatum of the mice after repeated METH treatments, using qRT‐PCR. Per2‐ overexpressed mice showed decreased locomotor sensitization and rewarding effects of METH compared to the wildtype mice, whereas the opposite was observed in Per2 knockout mice. Both types of transgenic mice showed altered expression levels of dopamine‐related genes after repeated METH administration. Specifically, we observed lower dopamine levels in Per2‐ overexpressed mice and higher levels in Per2‐ knockout mice. Taken together, Per2 expression levels may influence the addictive effects of METH through the dopaminergic system in the striatum of mice. Abstract : Per2‐ overexpressed mice showed decreased locomotor sensitization and rewarding effects of methamphetamine (METH) compared to wildtype mice, whereas the opposite was observed in Per2 knockout mice. Additionally, these transgenic mice exhibited altered expression levels of dopamine‐related genes after repeated METH administration. Taken together, Per2 expression levels may influence the addictive effects of METH through the dopaminergic system in the striatum of mice.